Neural correlates of error-related learning deficits in individuals with psychopathy - von Borries, A. K. L.; Brazil, I. A.; Bulten, B. H.; Buitelaar, J. K.; Verkes, R. J.; de Bruijn, E. R. A. (Psychological medicine, 2010)
Psychopathy (PP) is associated with a performance deficit in a variety of stimulus-response and stimulus-reinforcement learning paradigms. We tested the hypothesis that failures in error monitoring underlie these learning deficits. We measured electrophysiological correlates of error monitoring [error-related negativity (ERN)] during a probabilistic learning task in individuals with PP (n=13) and healthy matched control subjects (n=18). The task consisted of three graded learning conditions in which the amount of learning was manipulated by varying the degree to which the response was predictive of the value of the feedback (50, 80 and 100%). Behaviourally, we found impaired learning and diminished accuracy in the group of individuals with PP. Amplitudes of the response ERN (rERN) were reduced. No differences in the feedback ERN (fERN) were found. The results are interpreted in terms of a deficit in initial rule learning and subsequent generalization of these rules to new stimuli. Negative feedback is adequately processed at a neural level but this information is not used to improve behaviour on subsequent trials. As learning is degraded, the process of error detection at the moment of the actual response is diminished. Therefore, the current study demonstrates that disturbed error-monitoring processes play a central role in the often reported learning deficits in individuals with PP.